Active Aging Policies between Individual Needs and Collective Goods. A Study of Active Aging Policies and Practices in Norway - Midtsundstad, Tove; Bogen, Hanne (Nordic Journal of Working Life Studies, 2014)
A main objective of European governments is to reduce the number of early retirees, either by reforming pension systems or promoting active aging in working life. The importance of formulating a coherent personnel policy for all age groups is increasingly recognized by employers. However, there is still a lack of knowledge as how to strategically cope with an aging labor force. The aim of this article is to define and discuss a number of challenges arising from workplace-related active aging policies. We in particular discuss how an emphasis on economic incentives and gains (“senior goods”) may give rise to unanticipated side effects for the employers as well as the employees. The article is based on results from two recent studies: one study examining six Norwegian municipalities with seemingly good practices in work-related old age policies, and another examining such policies in eight establishments in four different industries.